The interaction and mutual development of “a maritime community with a shared future” and global ocean governance - Xu, Xiaowen; Zhang, Zhijun; Wang, Jinpeng (Frontiers in Marine Science, 2024)
As multilateralism evolves and China’s ocean awareness grows, China remains actively engaged in global ocean governance. The country has introduced the initiative of Building a Maritime Community with a Shared Future (MCSF), offering fresh perspectives for global ocean governance. The MCSF demonstrates both compatibility and adaptability with the evolving landscape of global ocean governance. This study is grounded in the historical context of the formation and evolution of China’s ocean consciousness within the broader framework of global ocean governance. Taking China’s contemporary ocean consciousness, the MCSF as the focal point, it analyzes the practical feasibility of integrating the MCSF with the evolving frameworks of global ocean governance. It is concluded that this integration process should involve ongoing review and refinement as the MCSF continues to develop.